Digital Image Steganography Based On Integer Haar Wavelet Transform And Coefficient Difference - Prajanto, Wahyu Adi (2014)
The development of digital information led to the demand for information security technology that protects the confidentiality of information. Digital steganography is one of such technology that able to protect the information from illegal interception due to its capability to hide the existence of the information without attracting the eavesdropper‟s attention. Among digital media, digital image is the most widely used media for steganography. Discrete Cosine Transform (DCT) is a well-known technique in digital image steganography, but the block calculation of DCT may pose artifact on the images. The disadvantages of DCT can be eliminating by the Discrete Wavelet Transform (DWT) which is more compatible with the Human Visual System (HVS). However the floating point of DWT can causes loss of information. On the other hand, Integer Wavelet Transform (IWT) is represented in finite precision numbers, which can avoid the problem of floating point precision of DWT. In this study, the messages are embedded on the wavelet coefficients of 1-level Integer Haar Wavelet Transform (IHWT) using Coefficient Difference scheme that adopted from Pixel Value Differencing (PVD). The messages are embedded on the difference value of two adjacent wavelet coefficients. Peak Signal to Noise Ration (PSNR) and Structural Similarity (SSIM) are used to measure the quality of stego image. The result shows that the proposed method has outperformed the existing method that employ IHWT and Pixel Mapping Method (PMM) in term of capacity vs. imperceptibility, as well as the maximum capacity. This is due to the high degree of Coefficient Difference that can tolerate larger modification of wavelet coefficients. Moreover, the Coefficient Difference can be applied on all coefficients instead of either significant or insignificant coefficient. These lead to the both high capacity and imperceptibility of digital image steganography system.